Saint Vincent and the Grenadines. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The planned transformation of the agricultural, forestry and fishing sectors is highlighted through new planning instruments. The Inter-American Institute for Cooperation on Agriculture (IICA) supported this process with the project "Support for the Development of an Agricultural Sector Plan and Sector Review for Saint Vincent and the Grenadines", including analysis of past performance and the formulation of new plans. Saint Vincent and the Grenadines strengthened its position as a regional leader in agri-food systems and enhanced South-South cooperation in agriculture. In addition, IICA contributed to strengthening business and association processes in the fishing sector, facilitating access to emerging opportunities. Business training was conducted and a business plan was developed for a fishing cooperative. Capacity development in agricultural health and food security was also promoted, with workshops on African swine fever preparedness and inter-institutional collaboration. Technical support was provided to a small agribusiness company to comply with HACCP regulations, improving its access to markets. Additionally, acceptable parties were trained in soil and water management, climate change adaptation, and natural approaches to crop protection. These initiatives contribute to climate resilience and the fulfillment of nationally determined contributions in the agricultural sector.